Shared decision-making for chronic obstructive pulmonary disease smoking cessation - Yen-Ping Tsai; Jiin-Torng Wu; Ming-Huang Chiu; Fang-Chun Wei (Intelektual Pustaka Media Utama, 2023)
Chronic obstructive pulmonary disease (COPD) is the main cause of death among people aged 65 years and above. Smoking cessation reduces the risk of morbidity and mortality. This study used the variables of smoking cessation behavior and psychological dependence to evaluate the effectiveness of smoking cessation shared decision-making (SDM) with traditional smoking cessation education in patients with COPD. This randomized controlled trial represents a significant positive correlation was observed among smoking duration (p<.05), the number of cigarettes (p<.05), smoking cessation behavior (p<.05), and psychological cigarette dependence. The intervention group (n=44) underwent session of smoking cessation SDM, whereas the control group (n=44) underwent session of traditional smoking cessation education. After three months of the intervention, significant improvements in psychological cigarette dependence (p<.05) and smoking cessation behavior (p<.05) were observed in both groups. The study confirmed that the success rate of smoking cessation in the intervention group is higher than the control group.